Modern Perspectives on Diagnosing and Treating Dry Eye Disease in Elderly Patients - Gródek, Aleksandra; Iskrzyński, Dominik; Dubiel, Mikołaj; Dubiel, Wiktoria; Obajtek, Patryk; Sopel, Anna; Sanakiewicz, Sylwia; Iglantowicz, Julia; Bułat, Aleksandra; Jasińska, Julia (Quality in Sport, 2026)
Dry eye disease (DED) is a common multifactorial disorder of the ocular surface characterized by tear film instability, ocular discomfort, visual disturbance, and chronic inflammation. The aim of this review was to summarise current evidence regarding the pathophysiology, risk factors, diagnosis, and management of dry eye disease, with particular emphasis on its impact in the elderly population. Material and methods. A narrative literature review with PRISMA-informed methodology was conducted using PubMed, Web of Science, and Google Scholar. Literature published within the last 10 years concerning dry eye disease, ocular surface aging, meibomian gland dysfunction, and treatment strategies was analysed. Results. Dry eye disease is strongly associated with age-related changes in the lacrimal glands, meibomian glands, ocular surface epithelium, and neural regulation of tear secretion. Additional contributing factors include systemic comorbidities, polypharmacy, hormonal alterations, and environmental exposures. The most common clinical manifestations include ocular irritation, dryness, burning, foreign body sensation, fluctuating vision, and reduced visual quality, all of which can significantly impair daily functioning and quality of life. Diagnosis is based on a combination of patient-reported symptoms and clinical assessment of tear film stability and ocular surface integrity. Management strategies include environmental modifications, artificial tear supplementation, anti-inflammatory therapy, autologous serum eye drops, punctal occlusion, scleral lenses, and surgical options in severe or refractory cases. Conclusions. Dry eye disease in elderly patients is a progressive, multifactorial condition requiring early recognition and individualized, stepwise management to prevent disease progression and optimize quality of life.